2014
DOI: 10.1002/lt.23909
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and electroencephalographic alterations before and after liver transplantation: What is reversible?

Abstract: The influence of liver transplantation (LT) on mental performance is debated, as is the role of pretransplant overt hepatic encephalopathy (OHE). The aim of this study was to evaluate the time course of the neuropsychological and electroencephalogram (EEG) features of patients with cirrhosis before and after LT with respect to prior OHE. The study population included 65 patients with cirrhosis on the transplant waiting list; 23 had a history of OHE. Each patient underwent an extensive psychometric assessment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 28 publications
5
92
0
Order By: Relevance
“…The type cognitive assessment throughout the studies includes several components that are affected in MHE, such as attention, concentration, psychomotor speed and verbal and visuospatial short-term memory. Therefore, most of the studies consider also the persistence or worsening of preexisting cognitive deficits as POCD [27][28][29]22,[37][38][39][40][41][42], in accordance with the statement that successful LT should remove HE [27,31,32]. MHE predicts OHE [43], but it is often clinically missed [44].…”
Section: Pocd In Lt Recipientsmentioning
confidence: 73%
See 2 more Smart Citations
“…The type cognitive assessment throughout the studies includes several components that are affected in MHE, such as attention, concentration, psychomotor speed and verbal and visuospatial short-term memory. Therefore, most of the studies consider also the persistence or worsening of preexisting cognitive deficits as POCD [27][28][29]22,[37][38][39][40][41][42], in accordance with the statement that successful LT should remove HE [27,31,32]. MHE predicts OHE [43], but it is often clinically missed [44].…”
Section: Pocd In Lt Recipientsmentioning
confidence: 73%
“…It is well know that MHE has high prevalence in patients with liver cirrhosis, ranging from 10% to 70% [28,29,22,37]. Instead, the prevalence of POCD across the studies ranges from 0% to 50% (see Table 1).…”
Section: Pocd In Lt Recipientsmentioning
confidence: 89%
See 1 more Smart Citation
“…Several studies have shown that cognitive function increases after orthotopic liver transplantation (OLT) [32,33,34]. However, some of the patients remain impaired, and thus attempts have been made to find out if significant cognitive impairment after liver transplantation depends on the grade of HE prior to HE or a history of HE.…”
Section: Mhe and Cognitive Function After Liver Transplantationmentioning
confidence: 99%
“…However, some of the patients remain impaired, and thus attempts have been made to find out if significant cognitive impairment after liver transplantation depends on the grade of HE prior to HE or a history of HE. Campagna et al [32] showed an improvement of cognitive function as well as EEG after liver transplantation in a study comprising 65 patients with cirrhosis. At the time of inclusion into the study none of the patients had overt HE, while 32% had mHE.…”
Section: Mhe and Cognitive Function After Liver Transplantationmentioning
confidence: 99%